Fatores-chave para construção de relacionamento de confiança no contexto das indústrias farmacêuticas de alta tecnologia e seus clientes - Prado, Maria Fernanda de Almeida (2017)
In the corporate environment, building trust relationships between trading partners has been a relevant strategy as a way of establishing consistent and lasting relationships. This concept echoes with particular force in high-tech pharmaceutical markets, in an attempt by manufacturers to gain a preferential position against a complex distribution chain and fierce competition. However, little has been published about trust premises, particularly in highly specialized markets. This study aims to understand what are the key factors in building a relationship of trust between high-tech pharmaceutical manufacturers and their customers. More particularly, it seeks to understand, for each category of health professional present in the client's relationship chain, whether the factors identified as trust premises are similar or different. To do so, the research was carried out in two stages, the first being a systematic, integrative bibliographical review on the theme “trust relationship”, which selected twentyfive articles that explicitly or implicitly approached the origin of trust. In this step, six key factors were found consistently in the literature. In the sequence, these factors were discussed in an exploratory qualitative research, with in-depth interviews with ten representatives of three groups of health professionals, working in clinics and hospitals, where these drugs are primarily prescribed and dispensed: clinical staff (physicians), operational (pharmacists or nurses) and administrative (commercial). The contribution of this study is, by clearly identifying such factors, allowing managers to adopt relationship marketing strategies more appropriate for their clients’ profile, better understanding the conditions necessary to generate relationships of trust between strategic partners. It is also to map nuances in the perceptions of the groups of health professionals surveyed, since they influence and decide on the purchase of high-cost products, and may demand specific strategies in the construction of the trust relationship.